On the impact of weather on German hourly power prices - Peter Kosater (University of Cologne, Seminar of Economic and Social Statistics, 2006)
The liberalization of electricity markets has triggered research in econometric modelling and forecasting of electricity spot prices. Moreover, both the demand and the supply of electricity are subject to weather conditions. Therefore, we examine the relation between hourly electricity spot prices from the European Energy Exchange and weather, represented by temperature and wind velocity. Furthermore, we assess whether the relation can be successfully exploited for forecasting. Thereby, we proceed in the framework of Markov regime-switching models which have become a workhorse in econometric modelling of electricity spot prices. As a result, we detect a strong relationship, on one hand. On the other hand, the significance of this relation for forecasting is confined to certain hours.
Keywords: Q40; L94; C22; 330; Electricity spot prices; Weather; Markov regime-switching